Analisis Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening pada PT. PLN APJ di Surakarta - Nadia, Nadia, Zulfa Irawati, S.E., M.Si (2015)
This study aimed to analyzed the influence of Transformatinal Leadership on Employee Performance, to analyze the influence of Tranformatinal Leadership on Job Satisfaction, to anlyze job satisaction as Intervening Variables of Transformational Leadership that influence Employee Performance in PT. PLN APJ Surakarta. The populations of research are all employees of PT. PLN APJ Surakarta. While the sample is 50 employees of PT. PLN APJ Surakarta with the sampling method used in this study is a convenience sampling and random sampling as the sampling technique. Data were analyzed using multiple linier regression analysis. Other analyzes include the classical assumption, hypothesis testing through F test, T test, te coeficient of determination (R2) and Path Analysis. Based on the results of study showed that variables of Transformational Leadership and Job Satisfaction have significant influence partially and together the Employee Performance. In addition, the Transformational Leadership variables sinificantly affect Job Satisfaction. Transformational Leadership and Job Satisfaction Employees can explain the performance of 87,6% and 12,4% can be explained by other variables outside the model. While Path Analysis result prove that the total effect is greater than direct effect that said job satisfaction as an intervening variable with Trnsformational Leadership that affect employee performance.